Pengaruh Harga dan Implementasi QRIS (Quick Response Code Indonesian Standard) terhadap Kepuasan Pelanggan di Koperasi FKIP Unmul - Indarwan, Panji; Haidar, Kadori; Sutrisno, Sutrisno (Peneliti.net, 2025)
In the midst of increasingly intense business competition, the level of customer satisfaction is an important element in determining the success of a company Price is an important component of a marketing strategy that has a significant impact on customer satisfaction. Customers often use price as an indicator of the value or quality of the product or service they purchase. The development of digital technology has also changed transaction patterns, one of which is through QRIS (Quick Response Code Indonesian Standard). This study aims to determine the influence of price and QRIS implementation on customer satisfaction in the FKIP Unmul Cooperative. This study uses a quantitative approach, with the population of all cooperative customers. The sampling technique used is purposive sampling, which is customers who have made payments through QRIS, with a sample of 68 people. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results showed that there was a partial and significant influence between price on customer satisfaction (significance 0.002 < 0.05), as well as between QRIS implementation on customer satisfaction (significance 0.000 < 0.05). Simultaneously, both also had a significant effect (significance of 0.000 < 0.05). The determination coefficient of 0.506 shows that 50.6% of customer satisfaction is influenced by price and QRIS implementation, while the remaining 49.4% is influenced by other factors.